2021
DOI: 10.1002/agj2.20860
|View full text |Cite
|
Sign up to set email alerts
|

Fodder biomass, nutritive value, and grain yield of dual‐purpose improved cereal crops in Burkina Faso

Abstract: In Burkina Faso, availability of quality feed is the major constraint on livestock productivity. Adoption of improved cereal cultivars among farmers could enhance fodder supply. This study assessed the potential for improved cereal cultivars to provide food and feed. The study sites were located in the Köppen climate Zone B (Katchari and Saria) and Köppen climate Zone A (Farakoba) in Burkina Faso (Beck et al., 2018). Five cultivars of pearl millet [Pennisetum glaucum (L.) R. Br.], nine cultivars of sorghum [So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thus, straws of improved variety of sorghum are sufficient to boost microbial activity in the rumen and improve ration degradation. The content obtained is higher than the results (3.96%) of Zampaligré et al [21] on the same variety. For cowpea haulms, the results obtained on the protein content (15.88%) are similar to that (18,5%) reported by Simian [22], higher than those (10.6%) reported by Azoutane et al [23], but lower than what Baba et al [24] obtained (21.3%) with an improved cowpea variety These differences could be explained by the varieties used, but also the conditions for collecting and storage of residues after harvesting the seeds.…”
Section: Chemical Composition Of Feedcontrasting
confidence: 73%
“…Thus, straws of improved variety of sorghum are sufficient to boost microbial activity in the rumen and improve ration degradation. The content obtained is higher than the results (3.96%) of Zampaligré et al [21] on the same variety. For cowpea haulms, the results obtained on the protein content (15.88%) are similar to that (18,5%) reported by Simian [22], higher than those (10.6%) reported by Azoutane et al [23], but lower than what Baba et al [24] obtained (21.3%) with an improved cowpea variety These differences could be explained by the varieties used, but also the conditions for collecting and storage of residues after harvesting the seeds.…”
Section: Chemical Composition Of Feedcontrasting
confidence: 73%
“…Although, there could be a great opportunity to improve forage availability through cropping [ 69 ] by using climate-resilient forage species. So far, research on forage species to cultivate in SSA had focused on dual-purpose cereals and legumes [ 70 ]; however, our study showed some interesting native grass and legume species to be introduced in agricultural systems.…”
Section: Discussionmentioning
confidence: 80%
“…Fst values between Group I and Group III was highest (0.121) followed by 0.118 between Group I and Group II and 0.113 between Group II and Group V. Mantel test indicated signi cant but weak (0.11*) association between morphological and molecular data. [27] also found non-signi cant genotypic variation for OM and CP in four maize cultivars. The use of large number of genotypes exhibits much signi cant variation as evident from ndings of [10].…”
Section: Amova Allelic Pattern Across Populations and Mantel Testmentioning
confidence: 75%